2001
DOI: 10.1152/ajpheart.2001.281.3.h1442
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to study contraction characteristics of a single cardiac myocyte using carbon fibers

Abstract: To facilitate cardiac muscle research, we developed a novel method by which the force and length of a single ventricular myocyte can be recorded with a pair of carbon graphite fibers attached firmly to both ends. One fiber was stiff, whereas the other fiber was compliant to allow the recording of force and shortening during twitch contractions. The image of the compliant carbon fiber was projected onto a pair of photodiodes, and their output was fed to a piezoelectric transducer after variable amplifications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 13 publications
1
58
2
1
Order By: Relevance
“…We monitored the sarcomere length in isolated rat cardiomyocytes during Ca 2ϩ waves. Hearts were removed from adult male Wistar rats (200 -300 g) that were under pentobarbital sodium anesthesia (50 mg/kg), and the left ventricular myocytes were isolated using enzymatic dissociation as described previously (35). Myocytes were suspended in 1.8 mmol/l Ca 2ϩ HEPES-Tyrode solution (in mmol/l: 137 NaCl, 5.4 KCl, 1.8 CaCl2, 0.5 MgCl2, 0.33 NaH2PO4, 5 HEPES, and 5 glucose, adjusted to pH 7.4 with NaOH at 22°C), transferred to a silicone-coated (Sigmacote; Sigma) glass chamber, and viewed using an inverted microscope (ϫ40 objective, IX71; Olympus).…”
Section: Cicr and Camentioning
confidence: 99%
“…We monitored the sarcomere length in isolated rat cardiomyocytes during Ca 2ϩ waves. Hearts were removed from adult male Wistar rats (200 -300 g) that were under pentobarbital sodium anesthesia (50 mg/kg), and the left ventricular myocytes were isolated using enzymatic dissociation as described previously (35). Myocytes were suspended in 1.8 mmol/l Ca 2ϩ HEPES-Tyrode solution (in mmol/l: 137 NaCl, 5.4 KCl, 1.8 CaCl2, 0.5 MgCl2, 0.33 NaH2PO4, 5 HEPES, and 5 glucose, adjusted to pH 7.4 with NaOH at 22°C), transferred to a silicone-coated (Sigmacote; Sigma) glass chamber, and viewed using an inverted microscope (ϫ40 objective, IX71; Olympus).…”
Section: Cicr and Camentioning
confidence: 99%
“…This CF technique has been used successfully for the characterization of cardiomyocyte electromechanical properties during auxotonic contractions (3,7,34). More recently, Yasuda et al (37), using a modified version of the CF technique, introduced an adaptive force-length (FL) control system. This technique has been used to subject individual cardiomyocytes to near-isometric, nearisotonic, and work-loop style contractions by anchoring one cell end with a stiff CF and dynamically controlling the attachment position of the other, compliant CF (21).…”
mentioning
confidence: 99%
“…The original model (29) reflects the strong cooperativity typical of the force-pCa relations observed experimentally (4). The values were adjusted to match the shortening data in our experimental study (10) and other parameters found in the literature, such as the rate of isometric force redevelopment in cardiac muscle (2,26), twitch force in intact myocytes (38), and the force-pCa curve in intact cardiac muscle (1) (see Fig. B2, E and F, in supplemental data for this article, which may be found at http://ajpheart.physiology.org/cgi/content/full/ 00425.2004.DC1).…”
Section: Force Production Formulationmentioning
confidence: 99%
“…Indeed, several parameters had to be based on data from permeabilized myocytes at low temperature or from entire cardiac muscle bundles. Recently, a new technique to measure force in intact cardiac myocytes has been developed using special carbon-fiber force transducers (38). With this technical advancement, it is hoped that tests such as force-pCa measurements [using TG (1); see Fig.…”
Section: Model Limitationsmentioning
confidence: 99%